Choriocapillaris Assessment In Patients Under Mek-Inhibitor Therapy For Cutaneous Melanoma: An Optical Coherence Tomography Angiography Study. (17th November 2021) - Fasolino, Giuseppe; Awada, Gil; Koulalis, Jorgos Socrates; Neyns, Bart; Van Elderen, Peter; Kuijpers, Robert W; Nelis, Pieter; Ten Tusscher, Marcel
ABSTRACT: Purpose: The present study investigates by optical coherence tomography angiography (OCTA) the retinal capillary plexus and choriocapillaris flow voids and their possible correlation with MEKAR. Methods: 34 eyes of 17 patients (61.5 years [30.4–77.4]) with stage IV cutaneous melanoma were included prospectively. All patients showed disease progression under treatment with Nivolumab/Ipilimumab and were subsequently treated with the MEK-inhibitor Trametinib 2 mg once daily. At the start and every 6 weeks during follow-up of 4 months, patients underwent a complete ophthalmologic exam, OCTA and when needed fluorescein angiography. Results: Statistical analysis was performed on 17 eyes of 9 patients. Eight patients were excluded due to missing OCTA images or due to drop-out because of decease or change of treatment. Comparing vessel area density ( P = .625 and 0.681, respectively), vessel skeleton density ( P = .996 and 0.766, respectively) of the superficial and deep capillary plexus, flow void number and total flow void area (mm 2 and %) ( P = .495; 0.197 and 0.298, respectively) of choriocapillaris slab, before and after treatment, revealed no significant difference. The evolution of choriocapillaris flow void parameter did not significantly differ in patients, who developed MEKAR compared to patients who did not. Conclusion: In patients receiving MEK-inhibitor with and without MEKAR, no significant different characteristics of the retinal capillary plexus and choriocapillaris were found. These data suggest that the development of MEKAR, has no correlation with vascular alteration.